Center Line Coordinates Survey for Existing Railway by 3-D Constraints Method - Hui Wei; Hongtao Zhu; Zhiyong Wang; Weijun Wu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Since the maintenance of HSR depends both on inner geometries and outer geometries information of track, it’s necessary that the survey technologies could measure the smoothness and coordinates of track in a high-density manner. But the existing technologies for track survey are either inaccurate or inefficient for HSR maintenance, the problem about track survey arises with the rapid development of high-speed rail (HSR) in China. To meet the demands on track smoothness survey of existing line, a method denoted as 3-D Constraints Method is introduced in this paper. The general principle of the method is obtaining center line locus with location information by means of survey trolley and CP-Ⅲ stakes. By measuring the distances between trolley and CP-Ⅲ stakes, the boundary condition could be determined. So, the problem of center line calculation is transformed into the problem of definite integral for FOG signals. Accordingly, an algorithm of coordinate calculation is given. With the constraints form CP-Ⅲ stakes, the coordinates of center line could be obtained in a defined accuracy. Finally, the simulation result shows that the method is effective. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2556